ChemInform Abstract: Highly Enantioselective Michael Addition of Malononitrile to α, β‐Unsaturated Pyrazolamides Catalyzed by a Bifunctional Thiourea. Issue 24 (27th May 2016) - Zheng, Yuanqin; Yao, Yongqi; Ye, Ling; Shi, Zhichuan; Li, Xuefeng; Zhao, Zhigang; Li, Xinying
Abstract: The Michael addition of malononitrile (II) to α, β‐unsaturated pyrazolamides [(I), (IV), (VI), or (VIII), resp.] is accomplished by the use of bifunctional thioureas as catalysts.